Cadmium-containing windmill-like heteropolyoxoniobate macrocycle with high yield for catalyzing Knoevenagel condensation. Issue 5 (23rd January 2023) - Liu, Zheng-Yi; Ye, Jian-Ping; Li, Yi-Lun; Sun, Yan-Qiong; Li, Xin-Xiong; Sun, Cai; Zheng, Shou-Tian
Abstract : A rare cadmium-containing windmill-like heteropolyoxoniobate macrocycle has been successfully synthesized with stable 1-D cyclic cluster aggregates. Abstract : A rare cadmium-containing windmill-like heteropolyoxoniobate macrocycle has been successfully synthesized with stable 1-D cyclic cluster aggregates. The compound exhibited promising basic catalytic ability for Knoevenagel condensation with a high yield under mild reaction conditions and high cycling stability. The theoretical calculation showed that the promising basic catalytic ability is due to the dense and stronger basic sites of the surface terminal O atoms.